Defamation and Insult Through Information and Communication Technology Media According to Law No. 19 of 2016 Concerning Amendments to Law No. 11 of 2008 Concerning Electronic Transaction Information - Surian Surian; Maya Jannah; Abdul Hakim (International Journal Labs, 2023)
This study examines Defamation and Insult through Information and Communication Technology Media According to Law No. 19 of 2016 Amendments to Law No. 11 of 2008 concerning Electronic Transaction Information which is the Indonesian Formil Law regarding the dissemination of information in the ITE Law, Criminal Code, Press Law, Human Rights Law, KIP Law and Constitutional Court Decision Number: 50 / PUU-VI / 2018, by using Normative Law research methods supported by the Concept approach (conceptual approach), Legislation approach (statue approach) and Case approach (case approach). The results of the author's research show that to be categorized as defamation, it must meet the elements contained in Articles 310 and 311 of the Criminal Code, namely